Analisis Kemampuan Inkuiri Mahasiswa Calon Guru SD pada Konsep IPBA untuk Pengembangan Perkuliahan Berbasis Inkuiri - Rosnita Rosnita; Ari Widodo; Enok Maryani; Bayong Tjasyono HK (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2011)
ABSTRACT- The research is aimed to know level of inquiry skill of elementary school teacher candidate as this type of skill is considered as appropropriate for achieving science skill processes during teaching and learning processes in scientific knowledge. This research follows the qualitative paradigm. To achieve the research goal, the data was collected upon 30 teacher candidates by using tests, observation, questionnaires, and     interview. The obtained data were descriptively analyzed. The result shows that inquiry skill level of elementary school teacher candidate is regarded as insufficient.